Contribution of competition in supporting medium, small and micro youth projects (Entrepreneurship Journal for Finance and Business, 2025)
This research aims to identify the contribution made by competition in helping young people implement their medium, small and micro projects, in order to ensure their success and achieve the desired goals, specifically in the early stages of establishing these projects. The research problem confirmed that many young people rely on the main pillars of competition (cost, quality, creativity, flexibility) in implementing their projects, but they do not have sufficient knowledge about their most important cognitive contents and how to invest them in competition with others. Accordingly, there is a cognitive deficiency more than a field deficiency in this field. As for the importance of the research, it was represented in presenting a set of proposals that contribute to enhancing the ability of the researched sample and society to invest in the relationship between competition and the success of youth projects (medium, small, and micro). Accordingly, this research aims to diagnose the reality of these two variables and discover the relationships of association and influence between them. To complete the research in its theoretical and field areas, the descriptive approach was adopted. The researchers also relied on a set of previous ideas in designing the questionnaire that was used in collecting data, after testing and adapting it to suit the Iraqi environment, which was distributed to a sample of young people with projects (medium, small, and micro) in the Shorjah area and the Arab market in Baghdad, numbering (376) individuals. The researchers also used measures of central tendency in processing the data from a statistical perspective using a set of tools available in the statistical program (SPSS.v23). These statistical tools provided researchers with a set of results that confirmed the application of the foundations of competition (cost, quality, creativity, flexibility), and youth projects (medium, small, and micro) to a high degree from a statistical point of view. Moreover, the foundations of competition contribute to a moral and statistical degree in enhancing the ability of youth to implement their projects and their success. Accordingly, the researchers recommended reviewing the world's experiences and the mechanisms that were adopted to encourage competition among youth, in addition to the support that was provided to them, whether materially or morally, and helping them build their various projects, and trying to transfer them to the Iraqi environment to invest their results and employ them in innovating various projects, whether (medium, small, and micro).